Thinking in a Non-native Language: A New Nudge? - McFarlane, Steven; Cipolletti Perez, Heather; Weissglass, Christine (Frontiers in Psychology, 2020)
The majority of research on how learning a second language (L2) has focused on the personal benefits of being bilingual or multilingual. In this paper, we focus on the potential positive effect of actively thinking in L2. Our approach is inspired by recent experimental research suggesting that actively thinking in an L2 leads to improved reasoning and decision-making, which is known as the foreign-language effect (FLE). We examine the possibility that one could selectively engage in L2 thinking in order to reap these potential benefits. Integrating this research with research in positive psychology, we explain how doing so might be understood as a type of “nudge,” or intervention that one could use to increase their chances of making autonomous decisions reflecting their own best interest. Nudges have been associated with improved outcomes with respect to many aspects of our lives - for instance sticking to goals, saving money, exercising more frequently, maintaining a healthy diet. It may be that bilinguals can assume an active role in increasing their happiness or well-being by making better decisions through strategic implementation of L2 in decision-making contexts. We also discuss the ethics of using the FLE as a nudge when it has beneficial consequences, as there are instances when doing so could be beneficial with respect to public policy as well. For instance, it has been shown that people are less averse to sustainable farming and eating practices (e.g. eating insects) when actively thinking in an L2. After reviewing the current research on the FLE, we suggest that further research needs to be done because actively thinking in L2 seems to function beneficially in some circumstances but may pose cognitive disadvantages in others.